Evaluación de un programa de secado para madera de Aliso (Alnus nepalensis D. Don) en el Centro de la Madera de la Universidad Nacional de Loja - Merino López, Jonathan Alexis (2023)
The solar dryer is an alternative to conventional methods because it reduces wood moisture, minimizing the investment and drying time. Therefore, the objective of this study was to evaluate the performance of a solar dryer for wood and its influence on the quality and drying time of Alnus nepalensis D. Don specimens. For this purpose, two drying programs were used at the Wood Center of the Universidad Nacional de Loja, one in a solar dryer and the other in an ambient dryer for 90 days with 12 specimens for each case. The climatic variables evaluated in both drying programs were: temperature, humidity and atmospheric pressure. The data were collected every minute during the entire drying time, and the weight was also systematically recorded, which allowed obtaining the drying kinetics curve. In addition, anhydrous moisture, drying defects, and workability of the dried wood were determined. The results showed that the drying chamber temperature is on average 8,33 °C higher than at ambient, the humidity is 23,30 % lower than at ambient and the pressure 17,66 hPa higher than in the ambient drying program. The drying curve showed 6,27 % less final moisture in the wood during the 90 days in the solar dryer. The wood placed in the solar dryer showed no bowing or cracking defects. In addition, the workability tests allowed classifying the Alnus nepalensis wood as of "good quality" for making furniture and joinery products. In conclusion, the use of the solar dryer by providing better climatic conditions reduces drying time, reduces the number of defects in the wood and improves workability. Therefore, the solar dryer is an excellent method at moderate costs and high quality.